Weak localization and weak antilocalization in doped Ge1-ySny layers with up to 8% Sn. (4th December 2020) - Weißhaupt, David; Funk, Hannes S; Kern, Michal; Dettling, Marco M.; Schwarz, Daniel; Oehme, Michael; Sürgers, Christoph; van Slageren, Joris; Fischer, Inga A; Schulze, Jörg
Abstract: Low-temperature magnetoresistance measurements of n- and p-doped germanium–tin (Ge1- y Sn y ) layers with Sn concentrations up to 8% show contributions arising from effects of weak localization for n-type and weak antilocalization for p-type doped samples independent of the Sn concentration. Calculations of the magnetoresistance using the Hikami–Larkin–Nagaoka model for two-dimensional transport allow us to extract the phase-coherence length for all samples as well as the spin–orbit length for the p-type doped samples. For pure Ge, we find phase-coherence lengths as long as (349.0 ± 1.4) nm and (614.0 ± 0.9) nm for n-type and p-type doped samples, respectively. The phase-coherence length decreases with increasing Sn concentration. From the spin–orbit scattering length, we determine the spin-diffusion scattering length in the range of 20–30 nm for all highly degenerate p-type doped samples irrespective of Sn concentration. These results show that Ge1- y Sn y is a promising material for future spintronic applications.